Modal Sosial, Konservasi dan Dinamika Pertanian Kentang di Dataran Tinggi Dieng - Nugroho Trisnu Brata; Moh Yasir Alimi; Muhammad Fauzan Ramadhan; Munadi Munadi (Universitas Negeri Semarang, 2025)
Potatoes are harvested from farms in the highlands and then present at the dinner table or become a snack for casual sitting companions. For some citizens of the world, potatoes are a staple food. In potato farming activities, social capital influences the relationships between actors, enabling potato production and distribution to develop and have an impact. The purpose of this study is to analyze the social capital operating in the dynamics of potato farming systems. The researcher used qualitative research methods, with data collection conducted through observation techniques, in-depth interviews, and literature studies. The research location is in Dieng Village, Kejajar District, Wonosobo Regency, Central Java Province. The field research will be carried out in July 2025. The research team stayed for a few days at residents' homes to more effectively gather observation data and conduct in-depth interviews in the morning, afternoon, or evening. Data were analyzed using analytical descriptive techniques, and data validity was assessed using triangulation techniques. The results of the research and discussion indicate that social capital in the potato farming system includes mutual trust, social or network relationships, and friendship or family. The social structure in the potato farming system consists of elements: farmers (owners, tenants, cultivators, laborers), brokers or intermediaries, and juragan. The role of brokers in the potato distribution process in Dieng Village is important because they act as connectors or intermediaries, facilitating information exchange between farmers. Meanwhile, telek brokers act as conservation agents and sellers of organic fertilizers to maintain the fertility of agricultural land.